Optimalisasi Sistem Informasi Akademik SMA Panca Moral Cikampek dengan SMS Gateway - Aryanti, Riska; Indrajit, Richardus Eko; Fitriani, Eka (www.bsi.ac.id, 2017)
Abstract – SMA Panca Moral Cikampek is a form of manifestation in guiding the younger generation in order to educate the nation of Indonesia, the increasing number of learners who are increasing each year from year to year, are required to provide information fast, precise and accurate. SMA Panca Moral Cikampek desperately needs an information system that support in the process of academic information services in the form of Short Message Service (SMS) gateway that can facilitate the students so that information obtained more quickly to be accepted by students. Short Message Service (SMS) is a facility to send and get text short message that many application on wireless communication scheme (wireless). To obtain the data searched based on the query from the user, forward or send the search results to the intended Short Message Service (SMS) then the query specified by this content is to apply information retrival algorithm with the N-Gram method and the biword index to group in certain categories more relevant. Kata Kunci:SMS gateway, information retrieval,N-Gram, index biword